ANALISIS KESALAHAN PILIHAN KATA PADA SURAT RESMI YANG DITULIS SISWA KELAS X SMK SWASTA BNKP DARO-DARO - Trisnawati Ziliwu; Rebecca Evelyn Laiya; Helnanirma Susanti Fau (Kohesi : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
This research is motivated by the use of word choice official letters that are not appropriate for class X students. The prpose of this study is to ini this research is descriptive qualitative method. The data sources are student worksheets. Data collection techniques, interview and documentation. The findings of the study indicate that in official letters wrriten by class X students, there are errors in word choice in terms of word accuracy. The dominant words are errors in the use of synonymous words,errors in the use of words with similar spellings, errors in changing meaning. This is due to the inadequate vocabulary that affects students’ ability to express their ideas through official letters. Based on the results of the study, it can be concluded that class X students do not understand the use of word choice correctly. Researchers suggest (1) students are more carefulin choosing words used in official letters, especially in using the correct language (2) further researchersto continue this research and develop it so that student’s ability to write formal letters becomes better.